Development and Validation of the International Extension Network Advocacy Capacity Scale - Kevan W Lamm; Alexa Lamm; Kristin E Davis; Catherine Dobbins; Alyssa Powell (Journal of International Agricultural and Extension Education, 2021)
Extension is sometimes viewed globally as less important than academic research and innovation, even though these networks are crucial to agricultural development. Using Lewin’s (1947) organizational change theory as a conceptual background, an instrument to measure advocacy capacity within international extension networks was developed. The resulting scale was analyzed for content validity, response process validity, internal structure validity, and consequential validity. An exploratory factor analysis (EFA) was performed on the proposed scale. The underlying structure of the scale was found to load onto five factors. The five extracted factors were labelled: 1) network support of advocacy, 2) network integration of advocacy, 3) network influence in advocacy, 4) network visibility in advocacy, and 5) network advocacy performance. The overall International Extension Network Advocacy Capacity (IENAC) scale, and associated subscales were all found to have acceptable levels of validity.
Keywords: Advocacy; international extension; scale development; rural advisory services; capacity assessment